Effects of the inclusion of glycerin in diets containing 30 or 70% roughage on feed disappearance and digestibility - Homem Junior, Antonio Carlos [UNESP]; Bertocco Ezequiel, Jane Maria; Cremasco, Leonardo Fernandes; Almeida, Marco Tulio Costa; Paschoaloto, Josimari Regina [UNESP]; D'Aurea, Andre Pastori [UNESP]; Perez, Henrique Leal (Univ Estadual Londrina, 2018)
The objective of this study was to evaluate in vitro nutrient disappearance and in vivo nutrient digestibility of cattle diets containing 70 or 30% roughage, with and without glycerin supplementation. Four Nellore cattle were used in the study based on a 4 x 4 Latin Square design in a 2 x 2 factorial arrangement. Inclusion of glycerin and roughage proportion did not affect the nutrient disappearance of each ingredient (P > 0.05). Regardless of the inclusion of glycerin, a reduction in the proportion of roughage led to an increase (P < 0.05) in DMDis (64 vs. 72%), NDFDis (41 vs. 54%), and ADFDis (31 vs. 44%) of the total rations. Inclusion of glycerin resulted in an increase (P < 0.05) in DMD (70 vs. 62%) and a reduction (P < 0.05) in CPD (32 vs. 38%) and STD (82 vs. 74%). The diet containing 30% roughage led to higher (P < 0.05) DMD (67 vs. 65%) and CPD (35 vs. 33%) in comparison with the 70% roughage diet, but did not differ (P > 0.05) in STD (78%). Inclusion of glycerin at 20% of the total DM increased the utilisation of dietary DM without affecting the fibrous fraction of the diet. Glycerin supplementation in diets containing 70% roughage improves neutral detergent fibre digestibility.
Keywords: INDF; Glycerol; Ingredients; In vitro; In vivo; Total ration